Teachers’ Perception Towards The Model Of Jawi Writing In Malaysian Education System - Suhid, Asmawati; Abu Bakar, Kamariah; Abdul Mutalib, Lukman; Muhammad, Muhd Fauzi (International Journal of Interdisciplinary Social Sciences, 2008)
Jawi writing was very important in the Islamic Education system in the Malay Peninsular before the colonial period. The use of Jawi indeed was widespread during the period of the Malacca Sultanate. It was used as the tool for the transmission of knowledge, missionary work and written communication. The importance of Jawi in the Malay society then was amplified when it was also used in the administration of the Sultanate. However, the use of Jawi has not been emphasized in the post colonial period by the Ministry of Education; it is not fully used even in the Islamic Education subject. Indeed, Jawi has been sparingly used by the Islamic Education teachers in both the primary and secondary schools. Hence, there is a lack of interest among Malay pupils to learn Jawi, and consequently many of them today are unable to read and write in Jawi. Interestingly, the use of Jawi has been reviewed recently by the Malaysian government. This review has been positive towards Jawi leading to several significant actions being taken to keep alive the use of Jawi. One of the most important measures taken was the introduction of the j-QAF programme. It is based on the Malaysian Prime Minister’s initiative which stressed the importance of Jawi in the teaching of Islamic religious subjects. In this paper, a study was carried out to identify the Islamic Education teachers’ perception of the Jawi Model in the j-QAF programme, their perception towards pupils’ interest in the Jawi Remedial Classes, and their level of satisfaction towards the level of support to run this programme. A set of questionnaire was used to collect the data. The research findings were further discussed in the paper.